COMMUNITY EMPOWERMENT THROUGH BUSINESS PROGRAM INCREASING COMMUNITY INCOME EMPOWERING FAMILY WELFARE IN MATTAPPAWALIE KELAHAN PUJANANTING DISTRICT - Muliati; Muhammad, Mukmin; Sukmiah; Satriana (P3M Stia Al Gazali Barru and Meraja media, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal